A novel inexpensive electrochemical sensor for pyrazinoic acid as a potential tool for the identification of pyrazinamide-resistant Mycobacterium tuberculosis - Rueda D. (2018)
Tuberculosis (TB) is a significant cause of morbidity and mortality worldwide. The patient compliance with the long treatment regimens is essential for successful eradication. Pyrazinamide (PZA) shortens these regimens from 9 to 6 months, and therefore, improves treatment completion rates. Although PZA is a first-line medication for the treatment of TB, no simple or reliable assay to determine PZA resistance is yet available. In the presence of PZA, only susceptible Mycobacterium tuberculosis strains release pyrazinoic acid (POA). Therefore, the measurement and quantification of released POA is an indicator of PZA resistance.